Finite element analysis of case box tape sealer mechanism. (2020) - Singh, Anubhav Raj; Dixit, Anurag; Dhupal, Jyotiprakash
Abstract: Case box tape sealer mechanism owing its quick manual adjustment, these rugged units accurately and reliably seal runs of the same size cartons. These are used for a variety of markets including packaging viz. pharmaceutical, medical devices, manufacturing food and beverage, electronics, distribution centres and retail. In the present study, finite element analysis is performed on the case box tape sealer mechanism using ANSYS in conjunction with SOLIDWORKS (Lombard, 2009; Madenci and Guven, 2015). Transient structural test was executed to find the stresses, deformation and deformation-time graph. The present analysis may be extended in analysis for stress determination with varying connecting rod length.